2022
DOI: 10.1186/s12866-022-02722-8
|View full text |Cite
|
Sign up to set email alerts
|

RpoN is required for the motility and contributes to the killing ability of Plesiomonas shigelloides

Abstract: Background RpoN, also known as σ54, first reported in Escherichia coli, is a subunit of RNA polymerase that strictly controls the expression of different genes by identifying specific promoter elements. RpoN has an important regulatory function in carbon and nitrogen metabolism and participates in the regulation of flagellar synthesis, bacterial motility and virulence. However, little is known about the effect of RpoN in Plesiomonas shigelloides. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…putida [89]. RpoN-dependent expression was also described for the T6SSs of Plesiomonas shigelloides [156] , P. putida [157] , K. pneumoniae [51] and P. aeruginosa [158–160].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…putida [89]. RpoN-dependent expression was also described for the T6SSs of Plesiomonas shigelloides [156] , P. putida [157] , K. pneumoniae [51] and P. aeruginosa [158–160].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…is a positive regulator of the F1- and F3-T6SS from P. fluorescens [ 155 ], but a repressor of the K1-T6SS from P. putida [ 89 ]. RpoN-dependent expression was also described for the T6SSs of Plesiomonas shigelloides [ 156 ] , P. putida [ 157 ] , K. pneumoniae [ 51 ] and P. aeruginosa [ 158–160 ]. Moreover, additional sigma factors positively participate in T6SSs expression such as RpoS (σ 38 ) in K. pneumoniae [ 51 ] and Yersinia pseudotuberculosis [ 161 ] and RpoE (σ 24 ) in Pseudomonas plecoglossicida promotes T6SS-2 expression [ 162 ].…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…cDNA synthesis was performed using a PrimeScript™ RT reagent Kit (Invitrogen, Waltham, MA, USA). And qRT-PCR analysis was conducted on an Applied Biosystems ABI 7500 sequence detection system (Applied Biosystems, Foster City, CA, USA); meanwhile, the P. shigelloides gyrB gene was used as the internal control for qRT-PCR [5], and relative expression levels were calculated as fold change values using the 2 −∆∆CT method [52]. Each experiment was carried out in triplicate.…”
Section: Rna Isolation and Quantitative Real-time Polymerase Chain Re...mentioning
confidence: 99%
“…The genus Plesiomonas, represented by a single species, Plesiomonas shigelloides, is a gram-negative opportunistic pathogen associated with gastrointestinal and extraintestinal diseases in humans, such as acute secretory gastroenteritis, an invasive shigellosis-like disease, and a cholera-like illness [1][2][3][4]. P. shigelloides can grow in anaerobic and aerobic conditions, and it's important to control the expression of genes involved in biosynthetic pathways, nutrient absorption, macromolecule synthesis, and excretion systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…RpoN can bind with core RNA polymerase (RNAP) and regulate gene transcription [20,21]. Recent reports have shown that RpoN is essential for biofilm detachment, flagellar formation, motility, and virulence of V. alginolyticus and other pathogens [22][23][24]. RpoN also affects the flagellar biogenesis-dependent motility in Vibrio spp.…”
Section: Introductionmentioning
confidence: 99%